"Check Yourself": Mindfulness-Based Stress Reduction for Teachers of Students With Challenging Behaviors. (April 2019) - Haydon, Todd; Alter, Peter; Hawkins, Renee; Kendall Theado, Connie
In this article, we open with a discussion of stress and its potential impact on the teaching profession. We then follow with an empirical rationale for and steps in the implementation of potentially promising mindfulness-based stress reduction (MBSR) interventions for teachers, particularly teachers of students with emotional and behavioral disorders. Body scan, calm breathing, focused attention, and relaxation are highlighted. A list of resources for further use of MBSR is included.